Disruption of the Suprachiasmatic Nucleus Blunts a Time of Day-Dependent Variation in Systemic Anaphylactic Reaction in Mice - Yuki Nakamura; Kayoko Ishimaru; Yu Tahara; Shigenobu Shibata; Atsuhito Nakao (Journal of Immunology Research)
Anaphylaxis is a severe systemic allergic reaction which is rapid in onset and potentially fatal, caused by excessive release of mediators including histamine and cytokines/chemokines from mast cells and basophils upon allergen/IgE stimulation. Increased prevalence of anaphylaxis in industrialized countries requires urgent needs for better understanding of anaphylaxis. However, the pathophysiology of the disease is not fully understood. Here we report that the circadian clock may be an important regulator of anaphylaxis. In mammals, the central clock located in the suprachiasmatic nucleus (SCN) of the hypothalamus synchronizes and entrains peripheral circadian clock present in virtually all cell types via neural and endocrine pathways, thereby driving the daily rhythms in behavior and physiology. We found that mechanical disruption of the SCN resulted in the absence of a time of day-dependent variation in passive systemic anaphylactic (PSA) reaction in mice, associated with loss of daily variations in serum histamine, MCP-1 (CCL2), and IL-6 levels. These results suggest that the central SCN clock controls the time of day-dependent variation in IgE-mediated systemic anaphylactic reaction, which may provide a novel insight into the pathophysiology of anaphylaxis.